Development of a sprinter talent identification model in children aged 10–12 years - Perwira Bakti, Ananda; Widyah Kusnanik, Nining; Sri Wahjuni, Endang; Sahani, Kandilia (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
This study aimed to develop a talent identification model for sprinters based on anthropometric components, physical qualities, and biomotor abilities in children aged 10–12 years. A research and development model was employed. The sample consisted of 172 children aged 10–12 years, including 89 boys and 83 girls, all of whom were healthy. The development of a sprinter talent identification model using anthropometry, physical qualities, and biomotor abilities in children aged 10–12 years begins with identifying the problem, designing a model or product, and evaluating the model’s feasibility before producing the final product in the form of software. The study’s findings indicated that the talent identification model for boys sprinters is represented by the equation: D = -9.909 + (1.255 × Speed) + (0.062 × Flexibility) – (0.122 × Jump Height) + (6.011 × Auditory Reaction Time). For girls, the talent identification model is represented by the equation: D = 9.334 – (0.048 × Height) + (0.140 × Leg Length) + (4.759 × Anaerobic) – (2.111 × Speed) + (0.090 × Flexibility). It was concluded that in the model for developing sprinter talent identification in boys aged 10–12 years, four variables were selected: speed, flexibility, jump height, and auditory reaction time. For girls aged 10–12 years, five variables were selected: height, leg length, anaerobic capacity, speed, and flexibility. There are differences in the variables contributing to the development of a biological talent identification model for young sprinters.